Flood Management Strategy Based on Community Perception in Rajabasa Area, Bandar Lampung City - Pranahayu Sekar Winahyu; Az Zahra Putri Sugiarto; Tiara Tabitha; Nandi Haerudin; Rahmi Mulyasari (Journal of Geology and Exploration, 2023)
A flood is an event that occurs when an excessive volume of water flow submerges land. Bandar Lampung is one area that has the potential for flooding. Floods that occur in the Rajabasa area are caused by disturbances to the balance of nature due to human activities. In this case, this study aims to determine the coping strategy before the flood occurred in the Rajabasa area, to find out the coping strategy when a flood occurs in the Rajabasa area and the last is to find out the disaster management strategy after the flood in the Rajabasa area. The research method used was literature review such as journals and articles about flooding as a source of research carried out by collecting data and information about flooding and survey activities by distributing questionnaires to the public using the Google form as well as short and focused interviews with flood-affected communities. The results of this study indicate that the flood management strategy in the Rajabasa area of Bandar Lampung City, based on the community's point of view, is in the medium category, that is, the community already understands the coping strategy before the flood occurs, during the flood and after the flood occurs.